2016
DOI: 10.5430/jha.v5n2p62
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of quality improvement in healthcare: Patient-centered care and health information technology applications

Abstract: Objective: Quality improvement in the healthcare industry has evolved over the past few decades. In recent years, an increased focus on coordination of care efforts and the introduction of health information technology has been of high importance in improving the quality of patient care. Methods: In this review, we present a history of quality improvement efforts, discuss quality improvement in the healthcare industry, and examine quality improvement strategies with a focus on patient-centered care and informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 19 publications
(27 reference statements)
0
26
0
Order By: Relevance
“…The model also underpins the importance of innovation in promoting quality of care by introducing new working methods, techniques and tools into the care process. This association was analysed in previous studies which found, for example, that namely the new information technologies are a way of promoting personalized care by improving the decision‐making process and the quality of care (Cantiello, Kitsantas, Moncada, & Abdul, ).…”
Section: Discussionmentioning
confidence: 99%
“…The model also underpins the importance of innovation in promoting quality of care by introducing new working methods, techniques and tools into the care process. This association was analysed in previous studies which found, for example, that namely the new information technologies are a way of promoting personalized care by improving the decision‐making process and the quality of care (Cantiello, Kitsantas, Moncada, & Abdul, ).…”
Section: Discussionmentioning
confidence: 99%
“…There are also several recent papers suggesting that internationally and across medical specialities this pattern continues 4 5. During the 1990s, there was an increase in the application of QI techniques and processes to healthcare settings, which has accelerated over the past two decades 1. Knowledge of QI is now an established part of many emergency medicine curricula and engagement in QI often a requirement of regulatory bodies.…”
Section: What Is Qi?mentioning
confidence: 99%
“…Since the 1930s, there have been debates about the improvement in the quality of hospital services, since decision-making in the health sector requires an awareness of professionals and managers, since they live in a constantly changing scenario of care to ensure quality patient care and services. Since then, the creation of systems, cheklists, fiches, protocols, questionnaires, programs and policies have been gaining space and visibility in the discussions about hospital management planning (Feldman et al, 2005;Cantiello et al, 2016). Among the various sectors of a hospital there is radiodiagnosis, an extremely complex sector because it has different modalities of image acquisition that is used as one of the main tools for diagnosis of pathologies, monitoring of treatment and prediction of results, through ionizing radiation.…”
Section: Introduction:-mentioning
confidence: 99%